Differences in firing patterns along the dorsal-intermediate hippocampal axis in a fixed route during a change in emotional context - Troha, Ryan; Lee, Shang Lin (Tommy); Anam, Maya; Tavakoli, Sheela; Morte, Bailey; Stevenson, Ian H.; Markus, Etan J. (Frontiers in Systems Neuroscience, 2025)
The hippocampus plays a prominent role in spatial navigation and memory. However, differences exist along the hippocampus longitudinal axis in function and connectivity. The current study focuses on the dorsal and intermediate subregions of the hippocampus. Single unit CA1 activity was recorded in a fixed route task with a change in emotional valence. We hypothesized the intermediate subregion to show greater changes in general firing activity and place cell remapping in response to emotional change in context compared to the dorsal subregion. Animals were trained to run back and forth for food on a U-shaped maze. In half the trials, animals were presented with a tone which signaled an active shock zone at the apex of the maze. Therefore, animals alternated between “safe” and “unsafe” emotional states, while the spatial configuration of the maze stayed the same. Single-unit activity was recorded and cells were classified by their locations in dorsal hippocampus (DH), anterior intermediate hippocampus (aIH), and posterior intermediate hippocampus (pIH) as well as by spike waveform. Information content was lower and firing rate was higher in the pIH compared to the DH and aIH. A decrease in firing rate was seen in zones close to the shock zone across all three subregions. Contrary to our hypothesis, in well trained animals DH and aIH showed more place cell remapping in response to the tone compared to intermediate regions. Cells in these regions also showed a decrease in firing prior to receiving information regarding the next trial.